Peningkatan Literasi Zakat Pada Siswa Sekolah Dasar Negeri 2 Restu Buana - Dwi Cahyo, Edo; Fatma Khoiriyah (Swadaya: Jurnal Pengabdian Masyarakat, 2024)
Zakat is one of the five main pillars of the Islamic religion and is a financial obligation imposed on Muslims which is able to cleanse one's wealth of negative traits such as stinginess, greed and egoism. Apart from that, zakat is one way to get closer to Allah SWT and get rewards and blessings from him. Zakat law in Islam is mandatory for Muslims who have fulfilled certain conditions. Therefore, Real Work Lecture (KKN) students from IAIN Metro took the initiative to hold a program in the form of Zakat Literacy outreach so that the public could better understand their obligations regarding the obligation to pay Zakat. This socialization activity was carried out at SDN 1 Sumber Katon. Planning for this activity includes preparation and preparation of socialization materials about zakat literacy. The activity was carried out on February 22 2024 in the form of literacy outreach to class IV,V,VI students at SDN 2 Restu Buana. Socialization activities in the form of zakat literacy to increase public awareness among class IV,V,VI students at SDN 2 Restu Buana regarding the importance of zakat